Realization of the Najafi-Golestanian Microswimmer - Lagubeau, G (American Physical Society, 2016)
A paradigmatic microswimmer is the three-linked-spheres model, which follows a minimalist approach for propulsion by shape shifting. As such, it has been the subject of numerous analytical and numerical studies. In this Rapid Communication, an experimental three-linked-spheres swimmer is created by self-assembling ferromagnetic particles at an air-water interface. It is powered by a uniform oscillating magnetic field. A model, using two harmonic oscillators, reproduces the experimental findings. Because the model remains general, the same approach could be used to design a variety of efficient microswimmers. © 2016 American Physical Society.